Probabilistic Misbehaviour Identification in Delay Tolerant Network towards Trust Formation - Vetrivel, K; Kayalvizhi, R (International Journal of Computer Sciences and Engineering, 2025)
In a resource compelled system such as Delay Tolerant Frameworks (DTN), effective utilization of assets such as vitality is vital for optimum system performance. However, due to hubs mobility, frequency of experiences and, message transmission, most of node’s vitality in this type of system is continuously depleted. A node’s vitality in DTN plays an vital role in the success of conveying messages. The lower the vitality a hub has, the lower its possibility to convey messages across the network. Thus, a proper energy-effective steering convention should be selected for message transmission for DTN applications. This issue leads us to research on the vitality utilization of hubs in DTN. We reproduced and, compared several existing steering conventions and, assessed them in terms of normal remaining vitality and, number of dead nodes. Our results show that critical Attributes of these steering conventions contribute to either consuming low or high vitality in conveying messages under certain system settings.